Central Asia Cold Case: Siberian Pine Fingers New Suspects in Growth Decline CA 1700 CE - David M. Meko; Dina F. Zhirnova; Liliana V. Belokopytova; Yulia A. Kholdaenko; Elena A. Babushkina; Nariman B. Mapitov; Eugene A. Vaganov (Plants)
Tree-ring width chronologies of Pinus sibirica Du Tour from near the upper treeline in the Western Sayan, Southern Siberia are found to have an exceptional (below mean–3SD) multi-year drop near 1700 CE, highlighted by the seven narrowest-ring years in a 1524–2022 regional chronology occurring in the short span of one decade. Tree rings are sometimes applied to reconstruct seasonal air temperatures; therefore, it is important to identify other factors that may have contributed to the growth suppression. The spatiotemporal scope of the “nosedive” in tree growth is investigated with a large network of P. sibirica (14 sites) and Larix sibirica Ledeb. (61 sites) chronologies, as well as with existing climatic reconstructions, natural archives, documentary evidence (e.g., earthquake records), and climate maps based on 20th-century reanalysis data. We conclude that stress from low summer temperatures in the Little Ice Age was likely exacerbated by tree damage associated with weather extremes, including infamous Mongolian “dzuds”, over 1695–1704. A tropical volcanic eruption in 1695 is proposed as the root cause of these disturbances through atmospheric circulation changes, possibly an amplified Scandinavia Northern Hemisphere teleconnection pattern. Conifer tree rings and forest productivity recorded this event across all of Altai–Sayan region.